Monitoria: colaboração assistida idas e vindas para um processo de ensino-aprendizagem colaborativo - Caetano, Márcia Aparecida Tinoco Pereira (Universidade do Vale do Rio dos Sinos, 2018)
The objective of this research is to gather information that contribute to a better understanding of the cases of success in the academic recovery of the students, who, besides taking part in tutorial classes at the Colégio Santo Inácio/RJ, also receive help from their peers. This study focuses on observing students' relationship with knowledge and how a collaborative teaching-learning environment can be established. The reflections and analyses are based on a theoretical socio-interactionist framework that dialogues with the reality in which the participants of the process, including the researcher, are inserted. In order to better understand what the students involved really think and feel, two analytical tools have been applied: questionnaire and interviews with volunteer student monitors and students assisted by them. The results point to the recognition of the importance of the teacher in the classroom as a first contact with the intended knowledge. Students note, however, that there are times when receiving the help of a fellow student, academically more prepared, makes a difference in their learning process. Likewise, the student monitors recognize that they are also benefited by sharing knowledge with their peers, because they reinforce the content worked and can think of other possibilities of learning the same subject. The data point to Tutoria as an alternative learning environment, willing to welcome anyone who needs academic support and who cannot be left without assistance. It is evident the importance (?) of volunteer student monitors in this education project, which seeks to expand the possibility of academic success of students with difficulties and believes in education that goes beyond the academic.
Keywords: Educação; Tutoria; Ensino-aprendizagem; Pedagogia inaciana; Education; Mentoring; Teaching-learning; Pedagogia ignatia